2003
DOI: 10.1002/art.11325
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human tumor necrosis factor receptor (etanercept) for treating ankylosing spondylitis: A randomized, controlled trial

Abstract: Results. Treatment with etanercept resulted in dramatic improvement. The ASAS20 was achieved by 59% of patients in the etanercept group and by 28% of patients in the placebo group (P < 0.0001) at week 12, and by 57% and 22% of patients, respectively, at week 24 (P < 0.0001). All individual ASAS components, acutephase reactant levels, and spinal mobility measures were also significantly improved. The safety profile of etanercept was similar to that reported in studies of patients with rheumatoid arthritis or ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
390
5
25

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 688 publications
(445 citation statements)
references
References 18 publications
25
390
5
25
Order By: Relevance
“…Etanercept is a fully human recombinant protein, comprising two molecules of soluble TNF receptor p75 and the crystallisable fragment component of immunoglobulin G1, which speciWcally binds to and neutralizes TNF-alpha. Several clinical studies have shown that etanercept reduces disease activity in patients with spondyloarthropathies, including reactive arthritis and AS [4][5][6][7][8]. Similar results have been reported with inXiximab, a chimeric monoclonal antibody against TNF [9][10][11][12][13][14][15].…”
Section: Introductionsupporting
confidence: 53%
“…Etanercept is a fully human recombinant protein, comprising two molecules of soluble TNF receptor p75 and the crystallisable fragment component of immunoglobulin G1, which speciWcally binds to and neutralizes TNF-alpha. Several clinical studies have shown that etanercept reduces disease activity in patients with spondyloarthropathies, including reactive arthritis and AS [4][5][6][7][8]. Similar results have been reported with inXiximab, a chimeric monoclonal antibody against TNF [9][10][11][12][13][14][15].…”
Section: Introductionsupporting
confidence: 53%
“…These were followed by more stringent trials of INF [26][27][28][29][30], ETA [31][32][33][34], and most recently ADA [35], enrolling over 1000 patients with ankylosing spondylitis. These trials are summarized in Table 3.…”
Section: Adamentioning
confidence: 99%
“…According to the meta-analysis of randomized-controlled trials (RCTs), it became evident that all available TNFi-s (adalimumab, etanercept, infliximab and golimumab) exert similar effects on signs and symptoms of the axial components of the disease (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%